THE INTERCONNECTEDNESS PATTERN OF CRYPTOCURRENCIES AND ISLAMIC INVESTMENT CLASSES - Anwer, Zaheer (Journal of Islamic Monetary Economics and Finance, 2023)
This study explores the dynamic co-movement of Islamic asset classes and cryptocurrencies for the period 01 March, 2017 to 15 June, 2022 by employing Wavelet methodology. The Islamic investment classes are represented by Islamic equities, Islamic Socially responsible investments, Real estate investment trusts and Sukuk. The results reveal that in normal times, there is negligible co-movement of both the asset classes. By contrast, both the investment classes exhibit significant spillover effect during the health crisis period. An important implication from these findings is that both the asset classes offer diversification opportunity during normal times but not during extreme times.